The Influence of Ethics, Experience and Competency toward the Quality of Auditing with Professional Auditor Scepticism as a Moderating Variable. (31st May 2016) - Zarefar, Arumega; Andreas; Zarefar, Atika
Abstract: This research was purposed to prove empirically on effect of ethics, experience and competency of auditor toward the output of auditing and professional scepticism as moderating variables to the auditors at representative BPKP Province of Riau. This research population was all auditors who work at representative BPKP Province of Riau. All the population was as the research sample and the data obtained was analysed by using doubled regression analysis through SPSS Program software. 119 questioners were given to all auditors at Representative BPKP Province of Riau and just 104 questioners could be processed (87%). The result demonstrated the ethics, experience, and competency were taking effect toward the quality of auditing output. Professional auditor scepticism was moderating variable to variable which connects to ethics and experience toward the quality of auditing output. Meanwhile for variable which connects to competency toward the quality of auditing output wasn't moderating variable.